E-survey on venous leg ulcer among Dutch dermatologists - Reeder, S. W. I.; de Roos, K-P.; Vogels, R. J. M.; Neumann, H. A. M. (Phlebologie, 2013)
Aim: To get insight into the frequency of venous leg ulceration in the Dutch dermato-logic practice, and into how this profession treats this disease.Design:Material and Methods: An e-survey was conducted. To all Dutch dermatologists and residents dermatology an email was sent with an online link to a questionnaire on venous leg ulcers.Results: The overall response was 30 %. 83.5 % of the doctors usually treat their patients according to the guideline. The dermatologic practice consists on average of 73 patients (range 0-500; SD 93) with leg ulceration, and yearly 54 new leg ulcer patients (range 0-300; SD 50) are seen. 65 % of the patients are women, 80 % is more than 45 years of age and 55 % is older than 65. Of all ulcers, 77 % has a venous aetiology, of which 59 % has a primary cause. Mean time to heal is 74 days (range 4-200; SD 39). Per year, dermatologists admit on average 7 patients (range 0-50; SD 11) because of leg ulceration. Eventually, 47 % of the admitted patients are treated by skin transplantation.Conclusions: This questionnaire gives a good insight in the epidemiology, and the diagnostic and therapeutic regimen for patients with venous leg ulcers in Dutch dermatologic practice.
Keywords: E-survey; treatment; venous leg ulcer